2022
DOI: 10.1002/jmv.28164
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine‐induced binding and neutralizing antibodies against Omicron 6 months after a homologous BNT162b2 booster

Abstract: Evidence about the long‐term persistence of the booster‐mediated immunity against Omicron is mandatory for pandemic management and deployment of vaccination strategies. A total of 155 healthcare professionals (104 COVID‐19 naive and 51 with a history of SARS‐CoV‐2 infection) received a homologous BNT162b2 booster. Binding antibodies against the spike protein and neutralizing antibodies against Omicron were measured at several time points before and up to 6 months after the booster. Geometric mean titers of mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Several studies have demonstrated that neutralizing antibody level is correlated with vaccine-induced immune protection against SARS-CoV-2 symptomatic disease (Earle et al, 2021; Favresse et al, 2022; Khoury et al, 2021; Koch et al, 2021). Therefore, a higher level of NAb may represent a higher percentage of vaccine efficacy against severe infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that neutralizing antibody level is correlated with vaccine-induced immune protection against SARS-CoV-2 symptomatic disease (Earle et al, 2021; Favresse et al, 2022; Khoury et al, 2021; Koch et al, 2021). Therefore, a higher level of NAb may represent a higher percentage of vaccine efficacy against severe infection.…”
Section: Discussionmentioning
confidence: 99%
“…The third booster dose elicits a high immune response against infection (Akaishi et al, 2022; Wan et al, 2022). A field study demonstrated that the third dose increased vaccine effectiveness against disease severity (Accorsi et al, 2022, Favresse et al, 2022), and reduced hospitalization rates (Adams et al, 2022, Wan et al, 2022). Furthermore, a third dose vaccine increases neutralizing capacity against the Omicron variant in laboratory tests (Assawakosri et al, 2022a, Assawakosri et al, 2022b, Kanokudom et al, 2022a, Kanokudom et al, 2022b, Suntronwong et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a third dose vaccine increases neutralizing capacity against the Omicron variant in laboratory tests (Assawakosri et al, 2022a, Assawakosri et al, 2022b, Kanokudom et al, 2022a, Kanokudom et al, 2022b, Suntronwong et al, 2022b). Waning immunity after three doses appears to significantly reduce vaccine efficacy (VE) against infection at 3–6 months of follow-up (Favresse et al, 2022), and probably leads to breakthrough infections with the Delta/Omicron variants (Amanatidou et al, 2022). Recent studies have shown that a fourth dose of mRNA vaccine was associated with a reduced rate of symptomatic infection during the Omicron predominant period (Bar-On et al, 2022; Regev-Yochay et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the viral genome has undergone such a huge number of mutations, that the identity of the epitopes used to construct the immunoassays no longer reflects that of the circulating variants. The serum levels of anti-SARS-CoV-2 antibodies may thus be variably underestimated, up to the point that some anti-SARS-CoV-2 immunoassays are no longer capable to detect antibodies generated against the most recent circulating Omicron sublineages (e.g., BA.4/5, BA.2.75, BQ.1, XBB.1 and so forth) as recently shown by two independent studies [ 3 , 4 ]. These aspects are also crucial when assessing vaccine response by serology in selected populations, as endorsed by Alexopoulos et al [1] .…”
mentioning
confidence: 99%
“…These aspects are also crucial when assessing vaccine response by serology in selected populations, as endorsed by Alexopoulos et al [1] . In fact, the neutralizing potential of Omicron sublineages of antibodies developed after monovalent COVID-19 vaccination is no longer adequately reflected by the anti-SARS-CoV-2 serum levels measured by some commercial immunoassays [4] . For this purpose, plaque reduction neutralization tests and/or live virus micro-neutralization assays are obviously preferable [5] .…”
mentioning
confidence: 99%